2019
DOI: 10.1111/medu.13796
|View full text |Cite
|
Sign up to set email alerts
|

Transphobia rather than education predicts provider knowledge of transgender health care

Abstract: Purpose Transgender and gender diverse (TGD) patients face significant hurdles in accessing affirming, knowledgeable care. Lack of provider knowledge presents a substantial barrier to both primary and transition‐related care and may deter patients from seeking health care. Little is known about factors that affect provider knowledge or whether exposure to TGD health content during training is associated with improved knowledge among providers. Using the TGD Healthcare Knowledge Scale, this study aimed to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
90
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(101 citation statements)
references
References 45 publications
5
90
1
5
Order By: Relevance
“…This highlights the limitations of one-time interventions and call for longitudinal programming to produce more durable improvements. Stroumsa et al [95] caution that transphobia needs to be addressed specifically as a potential barrier to improved knowledge. Their study did not find any association between increased hours of education and improved knowledge, but found a negative association between transphobia and provider knowledge [95].…”
Section: What Educational Interventions Have Been Described?mentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights the limitations of one-time interventions and call for longitudinal programming to produce more durable improvements. Stroumsa et al [95] caution that transphobia needs to be addressed specifically as a potential barrier to improved knowledge. Their study did not find any association between increased hours of education and improved knowledge, but found a negative association between transphobia and provider knowledge [95].…”
Section: What Educational Interventions Have Been Described?mentioning
confidence: 99%
“…Stroumsa et al [95] caution that transphobia needs to be addressed specifically as a potential barrier to improved knowledge. Their study did not find any association between increased hours of education and improved knowledge, but found a negative association between transphobia and provider knowledge [95]. Gamble Blakey and Treharne [96] emphasize values cultivation as a starting point in educating about TGD healthcare, and argue that simply adding curricular content about gender-affirming care may not result in significant learning as this requires a sensitive and specific pedagogic discourse around values [97].…”
Section: What Educational Interventions Have Been Described?mentioning
confidence: 99%
“…Despite this clear need, transgender people face a host of structural barriers to accessing care, ranging from high rates of homelessness attributable to rejection and discrimination, through lack of knowledgeable and affirming clinicians, [15][16][17] to transphobia 18 and direct discrimination in health care settings. 19 In addition, many transgender people in the United States face barriers to insurance coverage for gender-affirming care.…”
mentioning
confidence: 99%
“…For example, a recent Midwestern study found that transphobia rather than formal education predicts the provider’s knowledge of TGNC healthcare. 24 We agree with Stroumsa and colleagues that medicine, as an institution, may need to reexamine the ‘hidden curriculum’ that helps perpetuate transphobia and trans erasure. 24 Related to the ‘hidden curriculum’, we opted to remove from our curriculum content focused on intersex conditions because faculty had prepared it in a manner inconsistent with gender-affirming cultural competency and terminology.…”
Section: Discussionmentioning
confidence: 69%